Block copolymer
By using block copolymers, composed of polylactic acid and polyester units, the shortcomings of polylactic acid materials in terms of biodegradability and hydrolysis resistance are solved, and excellent performance in activated sludge and compost are achieved.
Patent Information
- Application Number
- CN202380046572.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-06-14
- Publication Date
- 2025-02-07
AI Technical Summary
The existing polylactic acid materials have shortcomings in terms of biodegradability and hydrolysis resistance, making it difficult to show good biodegradability in a wider environment, while inhibiting annual degradation in the products.
Block copolymer is composed of block structural units mainly composed of polylactic acid units and block structural units mainly composed of polyester units. The polyester unit contains units from aliphatic diols and aliphatic dicarboxylic acids. With an average molecular weight of over 10,000, the specific structure of the polyester unit improves hydrolysis resistance.
Excellent biodegradability, hydrolysis resistance and operability in activated sludge and compost are achieved, and the problem of insufficient performance of polylactic acid materials in these environments is solved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to block copolymers with excellent biodegradability, hydrolysis resistance, and operability. Background Art
[0002] From the perspective of environmental protection, the development of bioplastics is in full swing. Polylactic acid, a bioplastic made from renewable resources such as corn produced by photosynthesis, is expected to be used in a wide range of fields.
[0003] However, it is well known that polylactic acid is more brittle than petroleum-based plastics, has poor viscosity, flexibility, impact resistance, and heat resistance, and is easily hydrolyzed. Therefore, the use of polylactic acid as a resin material is sometimes limited. As an attempt to improve the shortcomings of polylactic acid, for example, the following technologies have been studied: copolymerization of polyesters with various characteristics with polylactic acid, the addition of additives such as chain extenders and fillers to form a composition (for example, see patent documents 1 to 4), and the use of stereocomplexes of polylactic acid (for example, see patent document 5).
[0004] In addition, research has been conducted on the use of compositions containing polylactic acid, and for example, an adhesive composition using a biodegradable raw material that satisfies adhesive properties is disclosed (see, for example, Patent Document 6).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 9-100344
[0008] Patent Document 2: Japanese Patent Application Publication No. 2004-231772
[0009] Patent Document 3: Japanese Patent Application Publication No. 2005-330318
[0010] Patent Document 4: Japanese Patent Application Publication No. 2007-269842
[0011] Patent Document 5: Japanese Patent Application Publication No. 2011-153275
[0012] Patent Document 6: Japanese Patent Application Publication No. 2021-169586 Summary of the invention
[0013] Problems to be solved by the invention
[0014] It can be inferred that the resin or resin composition containing polylactic acid described in Patent Documents 1 to 6 has a certain degree of biodegradability. Here, biodegradability refers to the property of being finally decomposed into water and carbon dioxide by organisms such as microorganisms, and it is well known that the resin containing polylactic acid exhibits biodegradability in compost. However, due to the increase in environmental awareness, it is required to exhibit biodegradability in a wider range.
[0015] In addition, in order to suppress the progress of aging degradation in the final product formed of the resin material, it is necessary to have hydrolysis resistance. Therefore, it is necessary for bioplastics to have both biodegradability and hydrolysis resistance depending on the application.
[0016] It is further preferred that bioplastics are easy to handle as resin material.
[0017] Therefore, the subject of the present invention is to provide block copolymers with excellent biodegradability, hydrolysis resistance and operability in activated sludge and in compost.
[0018] Means for solving problems
[0019] The inventors of the present invention have thought of the following invention and found that it can solve the problem.
[0020] That is, the present invention is as follows.
[0021] [1] A block copolymer,
[0022] It contains a block structural unit (A) with a polylactic acid unit (a) as its main component and a block structural unit (B) with a polyester unit (b) as its main component.
[0023] The polyester unit (b) contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2), wherein the aliphatic diol (b1) is an aliphatic diol having 5 to 9 carbon atoms and having an alkyl group as a branch chain, and the aliphatic dicarboxylic acid (b2) has 5 to 12 carbon atoms, and,
[0024] The number average molecular weight of the above-mentioned block copolymer exceeds 10,000.
[0025] [2] The block copolymer according to [1], wherein
[0026] The content of the block structural unit (A) or more and 95% by mass is 100% by mass of the block structural unit (A) and the block structural unit (B) is 5% by mass or more and 95% by mass or less.
[0027] [3] The block copolymer according to [1] or [2], wherein
[0028] Both terminals of the main chain of the aliphatic diol (b1) mentioned above have hydroxyl groups.
[0029] [4] The block copolymer according to any one of [1] to [3], wherein
[0030] The aliphatic diol (b1) mentioned above is 3-methyl-1,5-pentanediol.
[0031] [5] The block copolymer according to any one of [1] to [4], wherein
[0032] The aliphatic dicarboxylic acid (b2) is adipic acid.
[0033] [6] The block copolymer according to any one of [1] to [5], wherein
[0034] The above-mentioned block structural unit (A) contains structural units from polyL-lactic acid or structural units from polyD-lactic acid.
[0035] [7] The block copolymer according to any one of [1] to [6], wherein
[0036] The melting point of the above-mentioned block copolymer is 125°C or more and less than 185°C.
[0037] Effects of the Invention
[0038] According to the present invention, block copolymers with excellent biodegradability, hydrolysis resistance, and operability in activated sludge and in compost can be provided. DETAILED DESCRIPTION
[0039] Hereinafter, an example of the embodiment of the present invention will be described. However, the embodiments shown below are examples for defining the technical ideas of the present invention, and the present invention is not limited to the following description.
[0040] In this specification, although preferred embodiments are shown, a preferred embodiment is also a preferred embodiment in which two or more preferred embodiments are combined. Regarding items expressed as numerical ranges, when there are multiple numerical ranges, their lower limits and upper limits can be selectively combined as preferred embodiments. In addition, when there is a description of a numerical range of "XX to YY", it means "above XX and below YY".
[0041] In this specification, "-to-unit" (here "-to" means a polymer) means "a structural unit derived from -to-." For example, "polylactic acid unit" means "a structural unit derived from polylactic acid," and "polyester unit" means "a structural unit derived from polyester."
[0042] In this specification, the "main chain" of a polymer indicates the longest molecular chain in the polymer molecule without any special description. In addition, "branched chain" means a molecular chain other than the main chain in a molecule.
[0043] In the present invention, "solid" means no fluidity at a normal temperature (23°C) and no pressurization.
[0044] The block copolymer of the present embodiment contains a block structural unit (A) mainly composed of a polylactic acid unit (a) and a block structural unit (B) mainly composed of a polyester unit (b), and has a number average molecular weight exceeding 10,000.
[0045] The inventors of the present invention have conducted various studies on treatment schemes for imparting a wide range of biodegradability, excellent hydrolysis resistance, and operability to block copolymers. As a result, the inventors of the present invention have found that the inclusion of block structural units (A) and block structural units (B) is an effective treatment scheme for imparting biodegradability in compost or even activated sludge and achieving excellent hydrolysis resistance. In addition, it has been found that when the number average molecular weight of the block copolymer is within a specific numerical range, it becomes solid and has excellent operability and excellent hydrolysis resistance.
[0046] The polyester unit (b) is characterized in that it contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2), wherein the aliphatic diol (b1) is an aliphatic diol having 5 to 9 carbon atoms and having an alkyl group as a branch chain, and the aliphatic dicarboxylic acid (b2) has 5 to 12 carbon atoms.
[0047] It is inferred from the above characteristics that the block structure unit (B) is easy to become an amorphous polymer, so when biodegradation is carried out, microorganisms can easily enter the polymer structure, and the wide range of biodegradability is excellent. In addition, it can be considered that the aliphatic diol (b1) has an alkyl group as a side chain, thereby improving the hydrolysis resistance. On the other hand, when the block structure unit (B) is not an amorphous polymer, it can be considered that it is difficult for microorganisms to enter the polymer structure, resulting in difficulty in biodegradation, and the effect of the present invention cannot be obtained. However, the block structure unit (B) is an amorphous polymer, which is only one factor affecting biodegradability and hydrolysis. This is because it can be considered that biodegradation and hydrolysis are carried out by various factors such as whether the composite microorganism recognizes the amorphous structure as food, whether the enzyme or microorganism is easy to approach, the steric hindrance of the main chain, the melting point, and the degree of crystallinity. Therefore, the effect of the present invention is not obtained as long as it is an amorphous polymer. In addition, the reason why the above-mentioned polyester unit (b) can achieve both a wide range of biodegradability and excellent hydrolysis resistance in an opposite relationship has not yet been determined.
[0048] [Block structural unit (A)]
[0049] 〈Polylactic acid unit (a)〉
[0050] The block structural unit (A) is composed of polylactic acid unit (a).
[0051] The “main component” refers to a unit having the highest content ratio among the units constituting the block structural unit (A). The “main component” is preferably a unit having the highest content ratio by mass percentage among the units constituting the block structural unit (A).
[0052] The content of the polylactic acid unit (a) in the block structural unit (A) is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 85% by mass or more, further preferably 90% by mass or more, and may be 100% by mass. In addition, the upper limit of the polylactic acid unit (a) contained in the block structural unit (A) is not limited, and is, for example, 100% by mass or less.
[0053] The polylactic acid constituting the polylactic acid unit (a) may be prepared by a direct condensation method of lactic acid or by a ring-opening polymerization method of lactide. As the lactic acid, for example, at least one selected from L-lactic acid, D-lactic acid, and DL-lactic acid may be used. As the lactide, for example, at least one selected from L-lactide, D-lactide, DL-lactide, and meso-lactide may be used.
[0054] In addition, polylactic acid can be poly-L-lactic acid, poly-D-lactic acid, poly-DL-lactic acid, or a stereocomplex polylactic acid obtained by mixing poly-L-lactic acid and poly-D-lactic acid. From the viewpoint of cost, availability of raw materials, and operability of block copolymers, polylactic acid is preferably poly-L-lactic acid, poly-D-lactic acid, and poly-DL-lactic acid, and more preferably poly-L-lactic acid and poly-D-lactic acid.
[0055] On the other hand, from the viewpoint of the cost of synthesis, complexity, and processability of block copolymers, polylactic acid is preferably not stereocomplex polylactic acid.
[0056] From the viewpoint of more excellent biodegradability and hydrolysis resistance, the block structural unit (A) preferably contains 70% by mass or more of structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid, more preferably 80% by mass or more, and even more preferably 90% by mass or more. For example, a technical solution in which the block structural unit (A) is composed of structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid, that is, structural units derived from poly-L-lactic acid or structural units derived from poly-D-lactic acid account for 100% by mass, is an example of a preferred embodiment.
[0057] <Units (a') other than polylactic acid unit (a)>
[0058] The block structural unit (A) may contain a unit (a') other than the polylactic acid unit (a) or may not contain it.
[0059] As the monomer constituting unit (a'), it is not particularly limited to the scope of not impairing the effects of the present invention.
[0060] The content ratio of the unit (a') in the block structural unit (A) is preferably 30 mass % or less, more preferably 20 mass % or less, further preferably 15 mass % or less, and even more preferably 10 mass % or less.
[0061] <Number average molecular weight of block structural unit (A)>
[0062] The number average molecular weight of the block structural unit (A) is preferably 1,000 to 100,000, more preferably 5,000 to 25,000, and even more preferably 8,200 to 15,000. Within the above numerical range, more excellent hydrolysis resistance can be exhibited.
[0063] It should be noted that in the case where the block copolymer has a plurality of block structural units (A), the number average molecular weight of the block structural unit (A) represents the total of all blocks.
[0064] The number average molecular weight of the block structural unit (A) can be obtained from the number average molecular weight of the block copolymer described later and the mass content rate of the block structural unit (A).
[0065] The number average molecular weight of the block structural unit (A) can be changed by adjusting the polymerization conditions of polylactic acid, for example.
[0066] [Block structural unit (B)]
[0067] The block structural unit (B) is mainly composed of polyester unit (b).
[0068] The “main component” refers to a unit having the highest content ratio among the units constituting the block structural unit (B). The “main component” is preferably a unit having the highest content ratio by mass percentage among the units constituting the block structural unit (B).
[0069] The content of the polyester unit (b) in the block structural unit (B) is preferably 50% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further preferably 85% by mass or more, particularly preferably 90% by mass or more, and may be 100% by mass. In addition, the upper limit of the content of the polyester unit (b) contained in the block structural unit (B) is not limited, and is, for example, 100% by mass or less.
[0070] The polyester unit (b) contains units derived from an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2). Specifically, the polyester unit (b) contains units derived from a polyester obtained by reacting an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2). The polyester unit (b) may contain units derived from monomers other than the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2), or may not contain them.
[0071] As monomers other than aliphatic diol (b1) and aliphatic dicarboxylic acid (b2), they are not particularly limited to the scope of not impairing the effects of the present invention.
[0072] The total amount of the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2) in the polyester unit (b) is preferably 90 mol % or more, more preferably 95 mol % or more, further preferably 99 mol % or more, and may be 100 mol %.
[0073] <Aliphatic diol (b1)>
[0074] The aliphatic diol (b1) is an aliphatic diol having 5 or more and 9 or less carbon atoms and having an alkyl group as a branch chain. The aliphatic diol has two hydroxyl groups. The aliphatic diol (b1) generally excludes geminal diols. It is preferred that the two hydroxyl groups of the aliphatic diol (b1) are primary hydrocarbon groups. "Primary hydrocarbon group" refers to a hydroxyl group bonded to a primary atom, preferably a hydroxyl group bonded to a primary carbon atom.
[0075] It should be noted that the "carbon number" is the carbon number of the entire aliphatic diol (b1) containing the carbon number of the above-mentioned alkyl group.
[0076] The "branch" of an aliphatic diol (b1) refers to a partial structure branching from the "main chain" in an aliphatic diol (b1), preferably its end is not bound to a hydroxyl group.
[0077] The "main chain" of the aliphatic diol (b1) preferably refers to a partial structure of a molecular chain consisting of a plurality of carbon atoms connecting the two primary hydroxyl groups in the molecule at both ends. Therefore, the two primary hydroxyl groups in the aliphatic diol (b1) are preferably located at both ends of the "main chain" in the aliphatic diol (b1). In other words, the aliphatic diol (b1) preferably has hydroxyl groups at both ends of the main chain. Thus, a block copolymer that is easy to react with a dicarboxylic acid, easy to manufacture a triblock copolymer, and has better biodegradability and hydrolysis resistance can be obtained.
[0078] If the carbon number of the aliphatic diol (b1) is less than 4, the hydrolysis resistance is at risk of deterioration. In addition, if the carbon number of the aliphatic diol (b1) is 10 or more, there is a risk of degradation in the biodegradability.
[0079] The carbon number of the aliphatic diol (b1) is preferably 6 or more and 9 or less.
[0080] Although the carbon number of the main chain of the aliphatic diol (b1) is related to the carbon number of the branched chain, it is preferably 2 or more and 8 or less, more preferably 3 or more, more preferably 4 or more, and more preferably 5 or more.
[0081] When the aliphatic diol (b1) has no alkyl branch, the block structural unit (B) is easily crystallized and the hydrolysis resistance of the block structural unit (B) may be deteriorated. Therefore, the block copolymer cannot exhibit wide-range biodegradability and excellent hydrolysis resistance.
[0082] In the aliphatic diol (b1), the number of branches is preferably 1 or 2, and more preferably 1. In addition, the branch is preferably at least one of a methyl group, an ethyl group, and a propyl group, more preferably at least one of a methyl group and an ethyl group, and further preferably a methyl group. In addition, when the aliphatic diol (b1) has a plurality of branches, each branch may be the same or different.
[0083] Examples of the aliphatic diol (b1) include 2,2-dimethyl-1,3-propanediol, 2-ethyl-1,3-propanediol, 2-methyl-2-ethyl-1,3-propanediol, 2-methyl-1,4-butanediol, 1,2-pentanediol, 1,3-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 1,4-pentanediol, 2-methyl-1,4-butanediol, The aliphatic diol (b1) is preferably at least one of 3-methyl-1,5-pentanediol and 2,4-diethyl-1,5-pentanediol, and more preferably 3-methyl-1,5-pentanediol.
[0084] One of the aliphatic diols (b1) may be used alone or two or more types of them may be used in combination.
[0085] <Aliphatic dicarboxylic acid (b2)>
[0086] The carbon number of aliphatic dicarboxylic acid (b2) is 5 or more and 12 or less.
[0087] If the carbon number of aliphatic dicarboxylic acid (b2) is less than 4, the hydrolysis resistance is at risk of deterioration. In addition, if the carbon number of the aliphatic dicarboxylic acid (b2) is 13 or more, there is a risk of deterioration in the biodegradability.
[0088] From the viewpoint of hydrolysis resistance, the carbon number of the aliphatic dicarboxylic acid (b2) is preferably 5 or more, more preferably 6 or more. From the viewpoint of biodegradability, the carbon number of the aliphatic dicarboxylic acid (b2) is preferably 10 or less, more preferably 8 or less.
[0089] Examples of the aliphatic dicarboxylic acid (b2) include glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and decanedicarboxylic acid. The aliphatic dicarboxylic acid (b2) is preferably adipic acid or sebacic acid, and more preferably adipic acid.
[0090] One of the aliphatic dicarboxylic acids (b2) may be used alone or in combination of two or more.
[0091] <Preferred combination of aliphatic diol (b1) and aliphatic dicarboxylic acid (b2)>
[0092] From the viewpoint of being able to exhibit more excellent biodegradability and hydrolysis resistance, the combination of 3-methyl-1,5-pentanediol and adipic acid and the combination of 2,4-diethyl-1,5-pentanediol and adipic acid are examples of preferred embodiments, and the combination of 3-methyl-1,5-pentanediol and adipic acid is an example of a more preferred embodiment.
[0093] <Ratio of aliphatic diol (b1) to aliphatic dicarboxylic acid (b2)>
[0094] The charging molar ratio [aliphatic diol (b1) / aliphatic dicarboxylic acid (b2)] when reacting the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2) is preferably 1.4 / 1 to 1 / 1.4, more preferably 1.2 / 1 to 1 / 1.2.
[0095] <Unit (b') other than polyester unit (b)>
[0096] The block structural unit (B) may contain a unit (b') other than the polyester unit (b) or may not contain it.
[0097] As the monomer constituting unit (b'), it is not particularly limited to the scope of not impairing the effects of the present invention.
[0098] The content of the unit (b′) in the block structural unit (B) is preferably 50% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, further preferably 15% by mass or less, particularly preferably 10% by mass or less.
[0099] <Number average molecular weight of block structural unit (B)>
[0100] The number average molecular weight of the block structural unit (B) is preferably 2,500 or more, more preferably 4,000 or more, and even more preferably 5,000 or more. The number average molecular weight of the block structural unit (B) is preferably less than 100,000, more preferably less than 50,000, even more preferably less than 40,000, even more preferably less than 36,000, even more preferably less than 25,000, and may be less than 20,000 or less than 15,000.
[0101] When it is within the above numerical range, the softness and impact resistance of the block copolymer tend to be excellent.
[0102] The number average molecular weight of the block structural unit (B) can be determined by gel permeation chromatography (GPC), and specifically can be measured according to the method described in Examples. In addition, the number average molecular weight of the block structural unit (B) can also be determined from the number average molecular weight of the block copolymer described below and the mass content of the block structural unit (B).
[0103] The number average molecular weight of the block structural unit (B) can be changed by adjusting the polymerization conditions of the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2), for example.
[0104] [Structural unit ratio]
[0105] The content of the block structural unit (A) is preferably 5 mass % or more than 95 mass % or less than 100 mass % of the block structural unit (A) and the block structural unit (B).
[0106] When the proportion of the block structural unit (A) is 5% by mass or more, the block copolymer tends to have better handleability. When the proportion of the block structural unit (A) is 95% by mass or less, the block copolymer tends to have better flexibility and impact resistance.
[0107] From the viewpoint of operability, the proportion of the block structural unit (A) is more preferably 10% by mass or more, and further preferably 15% by mass or more. In addition, from the viewpoint of flexibility and impact resistance, the proportion of the block structural unit (A) is more preferably 80% by mass or less, further preferably 75% by mass or less, further preferably 70% by mass or less, and further preferably 60% by mass or less.
[0108] The proportion of the block structural units (A) can be determined by 1 The H-NMR is obtained, and the measurement can be made by the method described in the Examples.
[0109] In addition, the total content of the block structural unit (A) and the block structural unit (B) in the block copolymer is preferably 90% by mass or more, more preferably 95% by mass or more, and may be 100% by mass. In addition, the upper limit of the total content of the block structural unit (A) and the block structural unit (B) in the block copolymer is not limited, for example, it is 100% by mass or less.
[0110] The block copolymer may contain or contain units other than block structural unit (A) and block structural unit (B).
[0111] Units other than block structural units (A) and block structural units (B), are not specifically limited to the scope of not detrimental to the effects of the present invention.
[0112] The content ratio of units other than block structural units (A) and block structural units (B) in the block copolymer is preferably 10 mass % or less, and more preferably 5 mass % or less.
[0113] [Number average molecular weight of block copolymer]
[0114] The number average molecular weight of the block copolymer exceeds 10,000.
[0115] If the number average molecular weight of the block copolymer is 10,000 or less, the block copolymer becomes liquid and there is a risk of deterioration of operability. In addition, hydrolysis resistance tends to deteriorate.
[0116] From the viewpoint of operability and hydrolysis resistance, the number average molecular weight of the block copolymer is preferably 12,000 or more, more preferably 15,000 or more, and even more preferably 18,000 or more.
[0117] From the viewpoint of processability, the number average molecular weight of the block copolymer is preferably less than 100,000, more preferably less than 82,000, further preferably less than 60,000, further preferably 58,000 or less, further preferably 44,000 or less, further preferably 35,000 or less, and may be 30,000 or less.
[0118] The number average molecular weight of the block copolymer can be obtained by gel permeation chromatography (GPC), and in particular, it can be measured by the methods described in the Examples.
[0119] The number average molecular weight of the block copolymer can be adjusted, for example, by the number average molecular weight of the block structural unit (B), the number average molecular weight of the block structural unit (A), and the number of each block structural unit. The number average molecular weight of the block structural unit (B) can be changed, for example, by adjusting the polymerization conditions of the aliphatic diol (b1) and the aliphatic dicarboxylic acid (b2). The number average molecular weight of the block structural unit (A) can be changed, for example, by adjusting the polymerization conditions of the polylactic acid.
[0120] [Block copolymer bonding form]
[0121] The combination form of the block copolymer is preferably a triblock type and a diblock type, and more preferably a triblock type. The block copolymer may also be a mixture of a triblock type and a diblock type. Specifically, the combination form is preferably [block structural unit (A)]-[block structural unit (B)]-[block structural unit (A)].
[0122] [Melting point of block copolymer]
[0123] The melting point of the block copolymer is preferably 125° C. to less than 185° C., more preferably 130° C. to 180° C., and further preferably 140° C. to 170° C. When the melting point of the block copolymer is within the above numerical range, the handleability, hydrolysis resistance, and biodegradability tend to be more excellent.
[0124] The melting point of the block copolymer can be obtained by a differential scanning calorimeter, and in particular, it can be measured by the method described in the Examples.
[0125] 〈Glass transition temperature of block copolymer〉
[0126] The glass transition temperature of the block copolymer is preferably −80°C or higher and −15°C or lower. When it is within the above numerical range, the softness and impact resistance of the block copolymer tend to be excellent.
[0127] From the viewpoint of low-temperature properties such as impact resistance at low temperatures, the glass transition temperature of the block copolymer is more preferably -20°C or lower, further preferably -25°C or lower, and may be -30°C or lower, -40°C or lower, or -50°C or lower.
[0128] The lower the lower limit of the glass transition temperature of the block copolymer is preferred, for example, it may be -75°C or more, -70°C or more, -65°C or more, or -60°C or more.
[0129] The glass transition temperature of the block copolymer can be obtained by differential scanning calories measurement, and in particular, it can be measured by the method described in the Examples.
[0130] (Hydrolysis resistance of block copolymers)
[0131] The hydrolysis resistance of the block copolymer can be evaluated, for example, by the following examples: after being dissolved in chloroform at 10% by mass, it is poured on a glass plate to make a film with a thickness of 200 μm, and then the test sample cut out in a way that becomes 0.15g of weight is immersed in 50mL of ion exchange water of pH7, placed at 50°C, and the number average molecular weight is measured at a predetermined time interval, thereby measuring the time when the number average molecular weight is less than 90% of the initial number average molecular weight. Although the hydrolysis resistance of the block copolymer is not particularly limited, the time when the number average molecular weight is less than 90% of the initial number average molecular weight is preferably 50 hours or more, more preferably 100 hours or more, more preferably 150 hours or more, more preferably 200 hours or more, particularly preferably 250 hours or more, and most preferably more than 400 hours. If the hydrolysis resistance of the block copolymer is within the above range, it is possible to use the block copolymer to manufacture products with excellent long-term reliability of mechanical properties.
[0132] (Biodegradability in compost of block copolymer)
[0133] The biodegradability of the block copolymer in compost can be measured, for example, by the method described in the examples based on ISO14855-2:2018. Although there is no particular limitation on the biodegradability of the block copolymer in compost, the decomposition rate after 15 days is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more. If the biodegradability of the block copolymer in compost is within the above range, for example, a product with a small environmental load and excellent compost biodegradability can be manufactured using the block copolymer.
[0134] (Biodegradability in activated sludge of block copolymers)
[0135] The biodegradability of the block copolymer in the activated sludge can be measured, for example, by the method described in the examples based on the method based on ISO14851:2019. Although the biodegradability of the block copolymer in the activated sludge is not particularly limited, the decomposition rate after 90 days is preferably 5% by mass or more. If the biodegradability of the block copolymer in the activated sludge is within the above range, for example, the block copolymer can be used to manufacture a product with excellent biodegradability and low environmental load in a drainage treatment facility.
[0136] [Method for producing block copolymer]
[0137] The method for producing block copolymers may adopt a well-known method of production.
[0138] (1) A well-known method for producing block copolymers may be, for example, a method of synthesizing a polyester constituting a polyester unit (b) and polymerizing the polyester and lactide.
[0139] The polyester can be synthesized by a known method. For example, the polyester can be synthesized by reacting an aliphatic diol (b1) and an aliphatic dicarboxylic acid (b2) using an esterification catalyst (eg, tin octylate, tin chloride, tin oxide).
[0140] When the polyester and lactide are polymerized, a ring-opening polymerization catalyst (eg, tin octylate, tin chloride, tin oxide) is preferably used. Examples of the polymerization reaction include solution polymerization, melt polymerization, and interfacial polycondensation, and any known polymerization reaction conditions may be used.
[0141] (2) Alternatively, a known method for producing a block copolymer may be used, for example, a method in which polylactic acid constituting the polylactic acid unit (a) and a polyester constituting the polyester unit (b) are separately synthesized and the polylactic acid and the polyester are reacted.
[0142] Polylactic acid can be synthesized by well-known methods. For example, polylactic acid can be synthesized by direct condensation method, or polylactic acid can be synthesized by ring-opening polymerization method.
[0143] When the polylactic acid and the polyester are polymerized, an esterification catalyst (eg, tin octylate, tin chloride, tin oxide) is preferably used. Examples of the polymerization reaction include solution polymerization, melt polymerization, and interfacial polycondensation, and any known polymerization reaction conditions can be used.
[0144] Example
[0145] The present invention will be specifically described below by way of Examples and Comparative Examples, but the present invention is not limited thereto.
[0146] The compounds used in the Examples and Comparative Examples are as follows.
[0147] 3-methyl-1,5-pentanediol (Made in Colali, Ltd.)
[0148] Adipic acid (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0149] Tin octylate (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0150] Toluene (manufactured by Kishida Chemical Co., Ltd.)
[0151] L-lactide (made by Tokyo Chemical Industry Co., Ltd.)
[0152] Methanol (made by Fujifilm Wakako Pure Chemical Co., Ltd.)
[0153] 2,4-diethyl-1,5-pentanediol (made by Tokyo Chemical Industry Co., Ltd.)
[0154] 2-methyl-1,3-propylene glycol (made by Tokyo Chemical Industry Co., Ltd.)
[0155] Succinic acid (manufactured by Tokyo Chemical Industry Co., Ltd.)
[0156] 1,4-Butanediol (made by Tokyo Chemical Industry Co., Ltd.)
[0157] The physical properties of the block copolymers in the Examples and Comparative Examples were measured or evaluated by the following methods.
[0158] (1) Number average molecular weight (Mn)
[0159] The number average molecular weight (Mn) of the block copolymer was determined by gel permeation chromatography (GPC) in terms of standard polystyrene. The Mn of the block structural unit (B) was determined from the Mn of the block copolymer and the mass content of the block structural unit (B).
[0160] 〈GPC measurement conditions〉
[0161] Device: GPC device "HLC-8220" manufactured by Tosoh Corporation
[0162] Separation column: "TSKgel SuperMultiporeHZ-M (column diameter = 4.6mm, column length = 15cm)" (2 pieces used in series)
[0163] Eluent: Tetrahydrofuran (THF)
[0164] Eluent flow rate: 0.35mL / min
[0165] Column temperature: 40°C
[0166] Detection method: Differential refractive index (RI)
[0167] Injection volume: 10 μL
[0168] Concentration: 1 mg / 1 mL (block copolymer / THF)
[0169] (2) Hard ratio (mass %) (mass content rate of block structural unit (A) with polylactic acid unit (a) as the main component)
[0170] pass 1The hardness ratio of the block copolymer was calculated by H-NMR. Based on the area ratio of the signal near 5.2 ppm from the polylactic acid unit and the signal near 0.9 ppm from the structural unit (B) with the polyester unit (b) as the main component in the obtained spectrum, the molar ratio of the block structural unit (A) to the block structural unit (B) was calculated. The mass ratio of the block structural unit (A) adjusted so that the total of the mass ratios was 100 was taken as the hardness ratio.
[0171] 〈 1 H-NMR measurement conditions
[0172] Device: "JNM-ECX400" manufactured by Japan Electronics Co., Ltd.
[0173] Solvent: deuterated chloroform
[0174] Measuring temperature: 50℃
[0175] Cumulative times: 1024 times
[0176] Measurement conditions: Heating rate 10℃ / min
[0177] (3) Biodegradability (composting)
[0178] The biodegradability in composting was measured according to the method in accordance with ISО14855-2: 2018. A was evaluated as A if the decomposition rate after 15 days was 20% by mass or more, B if it was 10% by mass or more and less than 20% by mass, C if it was 5% by mass or more and less than 10% by mass, and D if it was less than 5% by mass.
[0179] (4) Biodegradability (activated sludge)
[0180] Biodegradability in activated sludge was determined according to the method based on ISО14851:2019. If the decomposition rate after 90 days is 5 mass% or more, it is evaluated as A, and if it is less than 5 mass%, it is evaluated as B.
[0181] (5) Operability
[0182] The condition that the properties of the block copolymer at room temperature (23°C) was solid and the condition that the conditions of liquid were B.
[0183] (6) Hydrolysis resistance (h)
[0184] After dissolving the block copolymer in chloroform at 10% by mass, the block copolymer was poured onto a glass plate to prepare a film with a thickness of 200 μm, and then cut out to a weight of 0.15 g to prepare a test sample. The obtained test sample was immersed in 50 mL of ion exchange water at pH 7, placed at 50° C., and the number average molecular weight was measured at a predetermined time interval (specifically, every 50 hours), and the time until the number average molecular weight was less than 90% of the initial number average molecular weight was evaluated based on the plotted approximate curve.
[0185] It should be noted that if the above-mentioned elapsed time exceeds 400 h, ">400 h" is expressed in Tables 1-1 and 1-2.
[0186] (7) Melting point (℃)
[0187] The melting point of the block copolymer was measured by a differential scanning calorimeter according to the method described in JIS K7121: 2012. When a plurality of peaks were observed, the melting point of the peak from the highest temperature side was taken as the melting point of the block copolymer.
[0188] Device: "DSC822" made by Mettler Toledo Co., Ltd.
[0189] Measurement conditions: Heating rate 10℃ / min
[0190] (8) Glass transition temperature (℃)
[0191] The glass transition temperature of the block copolymer was measured by a differential scanning calorimeter using the method described in JIS K7121:2012.
[0192] Device: "DSC822" made by Mettler Toledo Co., Ltd.
[0193] Measurement conditions: Heating rate 10℃ / min
[0194] [Example 1]
[0195] 3-methyl-1,5-pentanediol and adipic acid were injected into a flask equipped with an apparatus capable of distilling off the generated liquid and a vacuum pump in a molar ratio of 3-methyl-1,5-pentanediol / adipic acid = 1.1 / 1, and tin octylate was added so that the total weight of 3-methyl-1,5-pentanediol and adipic acid was 0.1% by mass, and the mixture was heated at 160°C for 3 hours and 220°C for 3 hours under a nitrogen atmosphere and normal pressure, and the reaction was carried out while distilling off water. Then, the pressure was reduced to 2,000 Pa and the mixture was reacted for 3 hours, and then the pressure was reduced to 80 Pa and the mixture was reacted while appropriately confirming the number average molecular weight until the number average molecular weight reached 9,500, thereby synthesizing a polymer composed of a structural unit (B') having a polyester unit as the main component. After the reaction was completed, the pressure was returned to normal pressure, the temperature was cooled to 80°C, toluene was added to dilute the solid content concentration to 40% by mass, and the toluene solution was added to methanol in an amount twice the total amount of the solution. The supernatant was discarded, and methanol in an amount equal to the amount of the toluene solution was added again for washing. The supernatant was discarded, and the recovered insoluble components were dried at 40°C in a vacuum dryer to remove the organic volatile components, thereby obtaining a polymer composed of a structural unit (B') mainly composed of a polyester unit. 1 H-NMR determination confirmed that the structures at both ends were mainly hydroxyl groups derived from 3-methyl-1,5-pentanediol.
[0196] Toluene was added again to the purified polymer composed of structural unit (B′) to dilute the polymer to a solid content concentration of 33% by mass, and then the temperature was raised to 140° C. to distill off 10% by mass of the added toluene, thereby dehydrating the system.
[0197] The mixture was then cooled to 80°C, and a polymer composed of structural unit (B') and L-lactide were added in a mass ratio of polymer composed of structural unit (B') / L-lactide = 50 / 50, and the weight of toluene removed by distillation was further added to adjust the solid content concentration to 50% by mass. The mixture was then heated to 100°C, and 0.1% by mass of tin octylate was added relative to the polymer composed of structural unit (B'), and the mixture was reacted for 4 hours to obtain a toluene solution of a block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit (b).
[0198] Toluene is added to the solution to dilute the solid content to 40% by mass, and then the toluene solution is added to methanol in an amount twice the total amount of the solution to precipitate the solid. The methanol in the supernatant is discarded, and an amount of methanol equal to the amount of the toluene solution added is added again for washing. The methanol is discarded, and the recovered solid is dried at 40°C in a vacuum dryer to remove the organic volatile components, thereby obtaining a block copolymer composed of a block structural unit (A) with a polylactic acid unit (a) as the main component and a block structural unit (B) with a polyester unit (b) as the main component. By the obtained block copolymer 1 H-NMR measurement confirmed that the peaks derived from the methylene groups adjacent to both ends of the hydroxyl groups in the polymer composed of the structural unit (B') disappeared, and a triblock structure composed of a structure of [block structural unit (A)]-[block structural unit (B)]-[block structural unit (A)] was mainly generated.
[0199] The above-mentioned measurement and evaluation were performed for the obtained block copolymer, and the results are shown in Tables 1-1. The obtained block copolymer has good operability, biodegradability and hydrolysis resistance.
[0200] [Examples 2 to 5]
[0201] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit (b) was synthesized in the same manner as in Example 1, except that the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit, the mass ratio of the L-lactide used was changed, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0202] The above-mentioned measurements and evaluations were performed for the obtained block copolymer. The results are shown in Table 1-1. The obtained block copolymer has good operability, biodegradability and hydrolysis resistance.
[0203] [Example 6]
[0204] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit (b) was synthesized in the same manner as in Example 1, except that 2,4-diethyl-1,5-pentanediol was used instead of 3-methyl-1,5-pentanediol and the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit.
[0205] The above-mentioned measurements and evaluations were performed for the obtained block copolymer. The results are shown in Table 1-1. The obtained block copolymer has good operability, biodegradability and hydrolysis resistance.
[0206] [Comparative Example 1]
[0207] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit (B) composed mainly of a polyester unit (b) was synthesized in the same manner as in Example 1, except that the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit, the mass ratio of the L-lactide used was changed, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0208] The above-mentioned measurements and evaluations were performed on the obtained block copolymer. The results are shown in Table 1-2. It should be noted that the melting point of the obtained block copolymer was not observed, probably because the number average molecular weight was too low.
[0209] The block copolymer obtained in Comparative Example 1 did not have good handleability and had lower hydrolysis resistance than that of the examples. This result is considered to be due to the excessively low number average molecular weight of the block copolymer.
[0210] [Comparative Example 2]
[0211] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit composed mainly of a polyester unit was synthesized in the same manner as in Example 1, except that 2-methyl-1,3-propanediol was used instead of 3-methyl-1,5-pentanediol, the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of a structural unit (B') composed mainly of a polyester unit, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0212] The above-mentioned measurements and evaluations were performed for the obtained block copolymer. The evaluation results are shown in Tables 1-2.
[0213] The block copolymer obtained in Comparative Example 2 was a result of low hydrolysis resistance compared to Examples. The reason for this result is that the carbon number of diol used as raw materials is less than 5.
[0214] [Comparative Example 3]
[0215] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit composed mainly of a polyester unit was synthesized in the same manner as in Example 1, except that succinic acid was used instead of adipic acid, the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of the structural unit (B') composed mainly of a polyester unit, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0216] The obtained block copolymer was measured and evaluated above. The evaluation results are shown in Tables 1-2.
[0217] The block copolymer obtained in Comparative Example 3 was a result of low hydrolysis resistance compared to Examples. It can be considered that the reason for this result is that the carbon number of dicarboxylic acid used as the raw material is less than 5.
[0218] [Comparative Example 4]
[0219] A block copolymer composed of a block structural unit (A) composed mainly of a polylactic acid unit (a) and a block structural unit composed mainly of a polyester unit was synthesized in the same manner as in Example 1, except that 1,4-butanediol was used instead of 3-methyl-1,5-pentanediol, succinic acid was used instead of adipic acid, the number average molecular weight was adjusted by adjusting the reaction time during the synthesis of the polymer composed of the structural unit (B') composed mainly of a polyester unit, and the dilution concentration during the synthesis was appropriately changed to a concentration that is easy to handle.
[0220] The obtained block copolymer was measured and evaluated above. The evaluation results are shown in Tables 1-2.
[0221] The block copolymer obtained in Comparative Example 4 did not have good biodegradability and had lower hydrolysis resistance than the examples. This result is believed to be due to the fact that the dicarboxylic acid used as the raw material had less than 5 carbon atoms and the diol had less than 5 carbon atoms and had no alkyl branch.
[0222] [Table 1-1]
[0223]
[0224] [Table 1-2]
[0225]
[0226] The compounds represented by the abbreviations in Tables 1-1 and Tables 1-2 are as follows.
[0227] PLLA: Poly L-lactic acid
[0228] MPD: 3-methyl-1,5-pentanediol
[0229] DEPD: 2,4-diethyl-1,5-pentanediol
[0230] MPDiol: 2-methyl-1,3-propanediol
[0231] BD: 1,4-Butanediol
[0232] AA: Adipic acid
[0233] SA: Succinic acid
[0234] As shown in the examples, the block copolymer of the present embodiment containing a specific block structural unit (A) with a polylactic acid unit (a) as the main component and a block structural unit (B) with a polyester unit (b) as the main component has good biodegradability and hydrolysis resistance, and is excellent in handling due to being in a solid state. Therefore, the industrial applicability of the block copolymer of the present embodiment is extremely high.
Claims
1. A block copolymer comprising a block structural unit A mainly composed of a polylactic acid unit a and a block structural unit B mainly composed of a polyester unit b, The polyester unit b contains units derived from an aliphatic diol b1 having an alkyl group as a branch and having a carbon number of 5 or more and 9 or less, and an aliphatic dicarboxylic acid b2 having a carbon number of 5 or more and 12 or less, and The block copolymer has a number average molecular weight exceeding 10,000.
2. The block copolymer according to claim 1, wherein The content of the block structural unit A is 5% by mass or more and 95% by mass or less relative to 100% by mass of the total of the block structural unit A and the block structural unit B.
3. The block copolymer according to claim 1 or 2, wherein The aliphatic diol b1 has hydroxyl groups at both ends of the main chain.
4. The block copolymer according to any one of claims 1 to 3, wherein The aliphatic diol b1 is 3-methyl-1,5-pentanediol.
5. The block copolymer according to any one of claims 1 to 4, wherein The aliphatic dicarboxylic acid b2 is adipic acid.
6. The block copolymer according to any one of claims 1 to 5, wherein The block structural unit A includes a structural unit derived from poly-L-lactic acid or a structural unit derived from poly-D-lactic acid.
7. The block copolymer according to any one of claims 1 to 6, wherein The melting point of the block copolymer is 125°C or higher and lower than 185°C.
Citation Information
Patent Citations
Polyactic acid block copolymer composition, its production and its molded product
JP1997100344A
Polyester composition and method for producing the same
JP2004231772A
High impact resistant polylactic acid composition
JP2005330318A
Resin for molding and polylactic acid resin composition containing the same
JP2007269842A
Polyester resin, resin composition and molded body using the same
JP2011153275A